2017
DOI: 10.1152/ajpcell.00273.2016
|View full text |Cite
|
Sign up to set email alerts
|

Distinct physiological effects of β1- and β2-adrenoceptors in mouse ventricular myocytes: insights from a compartmentalized mathematical model

Abstract: The β- and β-adrenergic signaling systems play different roles in the functioning of cardiac cells. Experimental data show that the activation of the β-adrenergic signaling system produces significant inotropic, lusitropic, and chronotropic effects in the heart, whereas the effects of the β-adrenergic signaling system is less apparent. In this paper, a comprehensive compartmentalized experimentally based mathematical model of the combined β- and β-adrenergic signaling systems in mouse ventricular myocytes is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…It showed the primary role of ␤ 1 -ARs in the inotropic response to stimulation with the ␤ 1and ␤ 2 -AR agonist isoproterenol. The model also demonstrated that the response to ␤ 2 -AR stimulation was only notable with the application of PTX or upon inhibition of PDE3 and PDE4 (22). However, it is interesting whether our model can simulate the experimental data obtained from TG mice overexpressing ␤ 2 -ARs after modifications and whether the model can reveal different responses of WT and TG mice to ␤-adrenergic stimulation.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…It showed the primary role of ␤ 1 -ARs in the inotropic response to stimulation with the ␤ 1and ␤ 2 -AR agonist isoproterenol. The model also demonstrated that the response to ␤ 2 -AR stimulation was only notable with the application of PTX or upon inhibition of PDE3 and PDE4 (22). However, it is interesting whether our model can simulate the experimental data obtained from TG mice overexpressing ␤ 2 -ARs after modifications and whether the model can reveal different responses of WT and TG mice to ␤-adrenergic stimulation.…”
Section: Introductionmentioning
confidence: 81%
“…Our model for the combined ␤ 1 -and ␤ 2 -adrenergic signaling system in mouse ventricular myocytes was able to explain only experimental data on WT mice (22). It showed the primary role of ␤ 1 -ARs in the inotropic response to stimulation with the ␤ 1and ␤ 2 -AR agonist isoproterenol.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Investigations about cAMP signaling have given rise to detailed mathematical models of the adrenergic pathways, including signaling compartmentation and the interaction J o u r n a l P r e -p r o o f with electrophysiological proteins [15][16][17]. Simulations including these models can improve mechanistic insight into HF pathophysiology, but investigations performed to date have generally focused on effects of electrical remodeling rather than on HFinduced alterations in the β-AR system.…”
Section: Introductionmentioning
confidence: 99%